Integrated proteomics analysis and network pharmacology to elucidate the mechanism of Zhilong Huoxue Tongyu Capsule alleviate hypertensive retinopathy in Ang II infusion mice model - Wu, Jiao; Xie, Wen; Xie, Yucen; Mazhar, Maryam; Duan, Junguo (Frontiers in Pharmacology, 2025)
BackgroundZhilong Huoxue Tongyu Capsule (ZLHXTY) has been used in clinical treatment of vascular diseases caused by hypertension over 20 years. However, the specific mechanisms by ZLHXTY alleviate hypertensive retinopathy (HR) needs to be further explored.Materials and methodsHR mouse model was established by infusing Ang II via subcutaneously implanted osmotic mini-pumps, followed by oral administration of ZLHXTY (0.35, 0.7, 1.4 g/kg/day) 28 days for treatment. To assess the impacts of ZLHXTY on retinal neurodegeneration and vascular injury, multiple experiments such as OCTA, ERG and HE staining were performed. Subsequently, network pharmacological and 4D-label-free proteomics to clarify the potential targets and mechanisms of ZLHXTY alleviated HR. Finally, Western blot, ELISA, IF, and other techniques were utilized to detect the expression of proteins related to inflammation, oxidative stress, and NLRP3 inflammasome activation.ResultsZLHXTY significantly alleviated retinal dysfunction, increased retinal blood flow, and mitigated pathological changes such as retinal tissues edema in HR mice. Network pharmacology indicated that ZLHXTY might exert anti-inflammatory and anti-oxidative stress effects through targets such as TNF and NF-κB. Proteomic analysis showed that the differential proteins between the ZL group and the Ang II group were mainly enriched in the immune-inflammatory response, and the main mechanism of which might be related to the assembly of NLRP3 inflammasome. Subsequent in vivo experiments corroborated that ZLHXTY remarkably attenuated inflammation and oxidative stress damage in retinal tissues. Further experiments demonstrated that ZLHXTY inhibited the NLRP3/Caspase-1/GSDMD signaling pathway and related protein expression. Finally, TEM results also verified that ZLHXTY alleviated pyroptosis in retinal cells.ConclusionOur results suggest that ZLHXTY by regulating the NLRP3/Caspase-1/GSDMD axis, inhibiting pyroptosis, thereby relieving retinal dysfunction and vascular injury in HR mice.